20-Hydroxyecdysone protects wheat seedlings from salt stress - Li, Jin-ting; Han, Xue-ping; Tang, Li; Wang, Can; Zhang, Wei-yu; Ma, Jianhui (Archives of Biological Sciences, 2018)
20-Hydroxyecdysone (20E), a molting hormone of insects, is the most abundant phytoecdysteroid (PE) produced by plants, where it represents a protective molecule against insect herbivores. The objective of the investigation is to determine the effect of 20E on the growth, physiological and biochemical characteristics and the transcript levels of antioxidant enzymes of wheat seedlings under salt stress. Our results showed that exogenous 20E was able to significantly alleviate salt-induced oxidative damage in wheat seedlings. It most likely acts by decreasing the concentration of malondialdehyde (MDA) and the rate of superoxide radical (O2•−) generation, and by increasing the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), concentrations of ascorbic acid (AsA) and glutathione (GSH), and the gene expression levels of SOD, POD, CAT. It was suggested that foliar spraying with 20E could efficiently protect wheat seedlings against salt-induced oxidative stress. The results also show that 20E had a positive physiological effect on the growth of salt-stressed seedlings. This is the first report dealing with the effect of 20E pretreatment in the enhancing of wheat seedling tolerance under salt stress. https://doi.org/10.2298/ABS170722056L Received: July 22, 2017; Revised: November 14, 2017; Accepted: December 11, 2017; Published online: December 22, 2017 How to cite this article: Li J, Han X, Tang L, Wang C, Zhang W, Ma J. 20-hydroxyecdysone protects wheat seedlings from salt stress. Arch Biol Sci. 2018;70(2):379-86.